Peran Legalitas Usaha dalam Meningkatkan Daya Saing UMKM di Desa Gunung Kijang - Hadli Lidya Rikayana; Al Lukman Syafni Isra; Fathur Rahman Ramadhan; Randi Febrian; Sahrul Nizam; Mesa Juliantri; Shalsabila Putri Zhalmi; Finia Ulfarianti; Marni Marni; Rifa Aprilisa (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
The Community Service Program (KKN) in Gunung Kijang Village, Bintan Regency, Riau Islands, was implemented with the aim of improving community welfare by assisting micro, small, and medium enterprises (MSMEs) in obtaining business legality. Legality is seen as an important requirement for increasing competitiveness, expanding market access, and ensuring product quality. In the digital age, business legality not only serves as legal protection but also opens up opportunities for wider access to various digital platforms, making it easier for business owners to reach global markets (Nicolas K.P. Adams,2023). This research uses a descriptive qualitative approach with a narrative method, employing data collection techniques such as field observation, in-depth interviews with MSME actors, and documentation including notes, archives, and activity photos. The research results show that the majority of MSME actors in Gunung Kijang Village do not yet have a Business Identification Number (NIB) or a Home Industry Food Permit (PIRT), which means their participation in the formal market is still very limited. This condition becomes even more challenging when faced with a global market that demands adequate access to information, training, and bookkeeping. However, this KKN program was able to encourage MSME actors to utilize digital technology as a means of promotion and marketing, while also raising awareness of the importance of business legality in business development. Thus, this activity has a sustainable positive impact on community empowerment, particularly in strengthening the position of MSMEs to become more competitive